2011
DOI: 10.4236/fns.2011.29131
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Compositional Values and Tissue Fatty Acid Profiles of Nile Tilapia (<i>Oreochromis niloticus</i> L.) Fed <i>Azolla</i>-Diets in Earthen Ponds

Abstract: The approximate general composition and the fatty acid profile of Nile tilapia fed Azolla-diets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…LA, ALA, ARA, and EPA levels in H. scabra were compared with other sea cucumbers and fishes. LA has also been detected at high levels in other sea cucumber, S. chloronotus (12.87%), and the Nile tilapia, Oreochromis niloticus (20.90%) [27]. The levels of ALA found in whole body and body wall of H. scabra were low and found very low in other sea cucumbers at 0 -1.88% [3,5], and fishes at 0 -1.86% [27,28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…LA, ALA, ARA, and EPA levels in H. scabra were compared with other sea cucumbers and fishes. LA has also been detected at high levels in other sea cucumber, S. chloronotus (12.87%), and the Nile tilapia, Oreochromis niloticus (20.90%) [27]. The levels of ALA found in whole body and body wall of H. scabra were low and found very low in other sea cucumbers at 0 -1.88% [3,5], and fishes at 0 -1.86% [27,28].…”
Section: Discussionmentioning
confidence: 97%
“…NA is found in sphingolipids, such as sphingomyelin in the myelin sheath of nerve fibers and in the white matter of animal brains [26]. NA was also found in other sea cucumbers at a much lower amount than in H. scabra, and was not detected in fishes [27,28]. NA supplementation is thought to improve neurological function [29] and enhance myelination in patients with demyelinating disease [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sudaryono [23] noted that A. pinnata inclusion in the diet of black tiger shrimp (P. monodon) reduced PER values. Additionally, Abou et al [29] recorded that PER progressively reduced from 0% to 50% substitution of fish meal with Azolla meal in Nile tilapia feeding.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to either poor absorption of the protein of supplementary A. pinnata by the fish or poor protein quality (amino acid composition). In a previous study, Abou et al [29] noted that FCR values rose from 0% to 50% substitution of Azolla filiculoides for Nile tilapia (Oreochromis niloticus L.). In contrast, Badwy et al [30] reported that up to 50% replacement of fishmeal with single-celled algae Chlorella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are an almost unique source of the health beneficial n-3 LC-PUFA, EPA and DHA, for humans 49 , 50 . Previously, higher levels of EPA, DHA and n - 3 PUFA were recorded in Nile tilapia fed diets including Azolla filiculoides 51 and duckweeds are a good source of ALA, that is the precursor of n-3 LC-PUFA 16 , 17 , 52 . Therefore, in the present study, one focus was to determine if dietary duckweed can boost the levels of n-3 LC-PUFA in carp.…”
Section: Discussionmentioning
confidence: 99%